The Influence of Gender and Resource Holding Potential on Aggressive and Prosocial Resource Control Strategy Choice in Early Childhood - Roberts, Alan Parry; Monks, Claire P.; Tsermentseli, Stella (Frontiers in Education, 2020)
Through the lens of resource control and resource holding potential theory, an investigation was conducted into the effect of resource opponent characteristics on frequency of aggressive and prosocial resource control strategy selection in 4-5-year-old boys and girls. Children (N = 92; 4-5 years old) were asked how they would respond to 12 hypothetical resource holding potential (RHP) vignettes, in which resource control opponents varied in ‘toughness’, ‘physical size’ and whether or not they were accompanied by friends. Girls gave significantly more prosocial responses to the vignettes than boys, and boys provided significantly more coercive responses compared to girls with some differences with age. Prosocial vignette responses were given significantly more frequently when the opponent was ‘not very tough’ as opposed to when they were ‘very tough’. Findings suggest that both boys and girls utilise some form of discrimination when deciding on how to respond to resource competition scenarios and that there are some age and gender differences in their reported response strategies. Findings are discussed in terms of resource control and RHP theory. Future study should investigate whether such differences translate into real-world observed resource control behaviour.